2021
DOI: 10.3390/ijerph18147535
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Flow Rate on a Third-Generation Sub-Ohm Tank Electronic Nicotine Delivery System—Comparison of CORESTA Flow Rates to More Realistic Flow Rates

Abstract: Many types of electronic cigarettes (ECs) are currently in use, but the default flow rate used to simulate puffing is centered on tobacco cigarette flow rates. CORESTA offers several methods and technical guides for evaluation of ECs but there are few puffing topography studies focusing on sub-ohm ECs; differences between real-world usage and that found in the literature appear large. This study focuses on how power and flow rate affect the nicotine yield of a sub-ohm EC. A puffing system (Puff3rd) has been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…The use of a CORESTA regime on devices intended for DTL vaping leads to the narrowing of the power range of the optimal regime range by decreasing its maximal power. This has been confirmed by experimental results reported by Soulet et al [8] (see Figure 2a below) and Floyd et al [52]. Therefore, experiments of this type can lead to overheating conditions, even under the power range required by the manufacturer.…”
supporting
confidence: 77%
“…The use of a CORESTA regime on devices intended for DTL vaping leads to the narrowing of the power range of the optimal regime range by decreasing its maximal power. This has been confirmed by experimental results reported by Soulet et al [8] (see Figure 2a below) and Floyd et al [52]. Therefore, experiments of this type can lead to overheating conditions, even under the power range required by the manufacturer.…”
supporting
confidence: 77%
“…In two recent extensive reviews, we highlighted this lack of information in numerous studies that looked at the presence of metals, aldehydes, free radicals and carbon monoxide in EC emissions 17 , 18 . The main problem we found was the testing of high powered subohm EC devices by puffing them with a low airflow rate, led to an excessive presence of toxic byproducts in the emissions, a phenomenon that does not occur when applying high airflow rates to these devices 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…At 4.8 V, nicotine levels were approximately 150, 400 and 1000 µg/puff for resistances of 1.5, 0.5 and 0.15 Ω, respectively. Floyd et al [54] reported nicotine yields of 66.6 165.6 and 198.4 µg/puff at 25, 50 and 75 W, respectively, using an atomizer with 0.5 Ω coil resistance. = calculated using the amount of E-liquid vaporized per puff, puff number, initial nicotine concentration and volume of E-liquid and maximal final volume of culture media.…”
Section: E-liquid Vaporization and Aerosol Deliverymentioning
confidence: 99%